Change in spatiotemporal cycle variables & muscle activation during ctasslc roller ski double poling technique - Kim, K.; Shin, I.-S.; Panday, S. B.; Kim, J.-H.; Kim, H.-Y.; Yu, G.-J.; Kim, J.-H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of the study was to assess the effects of distance covered while roller skiing using the double poling technique. Five national team members and college elite cross-country skiers were chosen to participate in this study. EMG system and digital camcorder were used to measure spatiotemporal cycle variables, muscular fatigue, and activation patterns. There were no significant differences on cycle variables. However, the result shows accumulation of fatigue and decrease of muscle activation on triceps brachii and tibialis anterior muscles across skiing distance.